N-(2,3-Dihydro-1,4-benzodioxin-6-yl)-4-fluorobenzenesulfonamide - Mughal, Shumaila Younas (International Union of Crystallography, 2012)
In the title compound, C(14)H(12)FNO(4)S, the dihedral angle between the aromatic rings is 50.26 (9)° and the C—S—N—C bond adopts a gauche conformation [torsion angle = −68.12 (15)°]. The dihydrodioxine ring is disordered over two orientations, which both approximate to half-chairs, in a 0.880 (7):0.120 (7) ratio. In the crystal, N—H⋯O hydrogen bonds link the molecules into C(4) chains propagating in [100]. Weak C—H⋯O and C—H⋯F interactions consolidate the packing.